Conceptualising contexts, mechanisms and outcomes for implementing large-scale, multisite hospital improvement initiatives: a realist synthesis. Issue 5 (19th May 2022) - Long, Janet C; Sarkies, Mitchell N; Francis Auton, Emilie; Nguyen, Hoa Mi; Pomare, Chiara; Hardwick, Rebecca; Braithwaite, Jeffrey
Abstract : Design: Realist synthesis. Study background: Large-scale hospital improvement initiatives can standardise healthcare across multiple sites but results are contingent on the implementation strategies that complement them. The benefits of these implemented interventions are rarely able to be replicated in different contexts. Realist studies explore this phenomenon in depth by identifying underlying context–mechanism–outcome interactions. Objectives: To review implementation strategies used in large-scale hospital initiatives and hypothesise initial programme theories for how they worked across different contexts. Methods: An iterative, four-step process was applied. Step 1 explored the concepts inherent in large-scale interventions using database searches and snowballing. Step 2 identified strategies used in their implementation. Step 3 identified potential initial programme theories that may explain strategies' mechanisms. Step 4 focused on one strategy-theory pairing to develop and test context–mechanism–outcome hypotheses. Data was drawn from searches (March–May 2020) of MEDLINE, Embase, PubMed and CINAHL, snowballed from key papers, implementation support websites and the expertise of the research team and experts. Inclusion criteria: reported implementation of a large-scale, multisite hospital intervention. RAMESES reporting standards were followed. Results: Concepts were identified from 51 of 381 articles. Large-scale hospital interventions were characterised by a top–down approach, external and internal support and use of evidence-based interventions. We found 302 reports of 28 different implementation strategies from 31 reviews (from a total of 585). Formal theories proposed for the implementation strategies included Diffusion of Innovation, and Organisational Readiness Theory. Twenty-three context–mechanism–outcome statements for implementation strategies associated with planning and assessment activities were proposed. Evidence from the published literature supported the hypothesised programme theories and were consistent with Organisational Readiness Theory's tenets. Conclusion: This paper adds to the literature exploring why large-scale hospital interventions are not always successfully implemented and suggests 24 causative mechanisms and contextual factors that may drive outcomes in the planning and assessment stage.